FORM OF JARANAN PEGON PAGUYUBAN MANGGOLO YUDO IN SUMBERGEDONG VILLAGE, TRENGGALEK DISTRICT - Dewi, Sanita Putri Tunggal; Handayani, enie Wahyuning (APRON Jurnal Pemikiran Seni Pertunjukan, 2024)
The purpose of this research is to examine the form of Jaranan Pegon Manggolo Yudo. The urgency of this research lies in the fact that this Jaranan is still an art heritage from the first generation that needs to be disseminated to preserve its originality. This Jaranan is unique in that it must be performed by four dancers symbolizing desires and the cardinal directions, dressed in wayang (shadow puppet) characters’ costumes. The researcher’s interest lies in its movements, which are still original, and its performance in the village cleansing ritual. The research problem formulated in this study is how the form of Jaranan Pegon Paguyuban Manggolo Yudo. This research employs a qualitative method with a descriptive type. Data collection techniques used include interviews, observations, and documentation, along with data analysis techniques based on field data. The research results show that Jaranan Pegon Paguyuban Manggolo Yudo has a unique structure not found in other dances, namely the ritual offering ceremony. Jaranan Pegon is almost similar to wayang orang (human wayang), with male characters wearing badong like the wayang character Gatotkaca and female characters like the wayang character Srikandi. The sampur (shawl) in Jaranan Pegon is used both as a costume and as a prop for dancing. The movements of this Jaranan are named according to the gending (musical accompaniment) performed, namely blitaran, jampiwangen, and sampak, which are repeated. Another unique aspect of this Jaranan Pegon is that the performance venue is at a belik, or a place considered sacred by the local community. Kata Kunci : Form, Jaranan Pegon, Manggolo Yudo